SURGICAL AND ONCOLOGICAL OUTCOMES IN WOMEN WITH ENDOMETRIAL CANCER TREATED VIA MINIMALLY INVASIVE SURGERY – A SINGLE-CENTER STUDY IN LOW-INCOME COUNTRY - Ibrahimov, A.M.; Gaziyev, A.Yu. (World of Medicine and Biology, 2024)
This single-center study’s main objectives were to analyze, especially in low-income countries the perioperative complications following minimally invasive surgery for uterine cancer, as well as the overall survival and recurrence rate. A retrospective analysis of the medical records of 117 patients with endometrial cancer who underwent laparoscopic and laparotomic operations was conducted. There were 95 endometrial cancer patients who had laparoscopic pelvic lymph node dissection and hysterectomy. The study excluded 22 women who had undergone laparotomic hysterectomy with dissection of the pelvic and aortic lymph nodes. There was no conversion from laparoscopy to laparotomy during the surgical process. A shorter hospital stay (≤4 days) was 74 (77.9 %). The longest observation duration was 77 months. The recurrence was recorded in twelve patients (12.6 %). During the follow-up period, survival data were gathered, and they revealed 83 (87.4 %) patients alive. So, laparoscopy demonstrates positive outcomes in the treatment of uterine-confined endometrial carcinoma.